In vivo spectroscopy and NMR metabolite fingerprinting approaches to connect the dynamics of photosynthetic and metabolic phenotypes in resurrection plant Haberlea rhodopensis during desiccation and recovery - Mladenov, Petko; Finazzi, Giovanni; Bligny, Richard; Moyankova, Daniela; Zasheva, Diana; Boisson, Anne-Marie; Brugière, Sabine; Krasteva, Vasilena; Alipieva, Kalina; Simova, Svetlana; Tchorbadjieva, Magdalena; Goltsev, Vasiliy; et al. (Frontiers in Plant Science, 2015)
The resurrection plant Haberlea rhodopensis was used to study dynamics of drought response of photosynthetic machinery parallel with changes in primary metabolism. A relation between leaf water content and photosynthetic performance was established, enabling us to perform a non-destructive evaluation of the plant water status during stress. Spectroscopic analysis of photosynthesis indicated that, at variance with linear electron flow involving photosystem (PS) I and II, cyclic electron flow around PSI remains active till almost full dry state at the expense of the linear electron flow, due to the changed protein organization of photosynthetic apparatus. We suggest that, this activity could have a photoprotective role and prevent a complete drop in adenosine triphosphate (ATP), in the absence of linear electron flow, to fuel specific energy-dependent processes necessary for the survival of the plant, during the late states of desiccation. The NMR fingerprint show significant metabolic changes in several pathways. Due to the declining of linear electron flow accompanied by biosynthetic reactions during desiccation, a reduction of the ATP pool during drought was observed, which was fully and quickly recovered after plants rehydration. We found a decline of valine accompanied by lipid degradation during stress, likely to provide alternative carbon sources for sucrose accumulation at late stages of desiccation. This accumulation, as well as the increased levels of glycerophosphodiesters during drought stress could provide osmoprotection to the cells.